The effect of porous materials on temperature drop in a standing wave thermoacoustic cooler - Mohd Saat, Fatimah Al Zahrah; Sukri, Mohamad Firdaus; Rosle, Nur Damia Asma; Raja Othman, Raja Nor Firdaus Kashfi; Saechan, Patcharin (Universiti Malaysia Perlis, 2022)
Thermoacoustics is a principle of sciences that offers an alternative solution for cooling system with a technology that is green and sustainable. The thermoacoustic energy conversion takes place mostly within the area of the porous structure that forms the core of the system. In this study, the effect of changing the material of the porous structure on the performance of the thermoacoustic refrigerating system is reported. Experiments were performed under standing wave environment with two different resonance frequencies with air at atmospheric pressure. The porous stack was chosen to be with three different materials of polycarbonate, ceramic and stainless steel. The results show that the use of ceramic celcor as the porous material provides the biggest temperature difference which means that thermoacoustic performance is better. The performance is even better when the system is working with higher resonance frequency. At atmospheric pressure condition with air as working medium, the thermoacoustic cooler with ceramic porous material is capable of producing temperature difference of 39.16C when operating at a frequency of 202.1 Hz.